Pandangan Ulama Kontemporer Terhadap Jual Beli Salam Pada Zaman Modern Dilihat dari Ekonomi Islam - Wahida Z (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2018)
In the sale and purchase agreement as-salam in modern times have differences with the sale and purchase agreement as-salam in the classical period. In the sale and purchase agreement of as-salam in modern times the concept of khiyar remains enforced but only with khiyar terms and khiyar ‘disability, because khiyar assemblies are not possible, involving long distances and the short period of order with modern systems. While in the sale and purchase transactionsregards in the third classical khiyar remain valid, because in conducting transactions buyers and sellers directly meet at the place of agreement. This study also discusses the guarantee in the sale and purchase agreement of as-salam in modern times reviewed according to Islamic law that the law is mandatory. Majority of contemporary scholars allow to guarantee in the sale and purchase agreement of as-salam, in order to help eliminate the burden of self-indebted people and aims to avoid hostilities, fights, and fraud between both parties.